Dynamics of Learning Characteristics of MI Children: A Literature Study for the Quality of Elementary Madrasah Education - Radhita Maharani Ramli; Ichsan; Fadiah Khoirunnisa Salkeri; Azzahrah Ramaputri Tilotama (Elementaria: Journal of Educational Research, 2025)
Characteristics are character, character, morals that are formed from the internalization of virtues so that they are used as a benchmark for points of view, thinking and behaving towards other people. According to the Big Indonesian Dictionary (KBBI), character is the nature, character, character that differentiates a person from other people. So it can be concluded that character is the traits, morals, habits that a person has to differentiate himself from other people and serve as a basis for acting. Students according to Law no. 20 of 2003, namely community members who want to develop their potential through educational institutions available in the path, level and type of education (Pusdiklat, National Library). Meanwhile, according to Sarwono, a student is someone who studies formally in the world of education. Educators (teachers) play an important role in the learning process in the classroom and even in improving the quality of education in a school, region and nationally. Teachers as a key component in the educational process are required to be able to carry out an educational learning process. This big role is required of teachers, especially in forming children's character and national character. This research uses qualitative research methods. According to Sukmadinata (2009), qualitative methods are research to describe and analyze phenomena, events, beliefs, attitudes and social activities individually and in groups. Qualitative methods are a collection of methods to analyze and understand more deeply the meaning of several individuals or groups considered as humanitarian problems or social problems.